2020
DOI: 10.1080/08941939.2020.1745964
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Results of Sclerotherapy with 3% Polidocanol Foam for Symptomatic Second- and Third-Degree Hemorrhoidal Disease

Abstract: Background: Hemorrhoidal disease (HD) is defined as the symptomatic enlargement and/or distal displacement of anal cushions and is one of the most common proctological diseases. Sclerotherapy (ST) with 3% polidocanol foam induces an inflammatory reaction with sclerosis of the submucosal tissue and consequent suspension of the hemorrhoidal tissue. The aim of this study was to evaluate the short-term effectiveness and safety of ST with 3% polidocanol foam for the treatment of symptomatic second-and third-degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 26 publications
3
41
3
Order By: Relevance
“…These results were consistent with a recent retrospective study [ 5 ], concerning the use of 3% polidocanol foam in 66 patients with II- and III- degree HD, in which the overall success rate after a single session was 78.8% and only 9 patients experienced a median post-operative pain of 4. There was no statistically significant difference between II- and III-degree HD in terms of success rate and complications.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…These results were consistent with a recent retrospective study [ 5 ], concerning the use of 3% polidocanol foam in 66 patients with II- and III- degree HD, in which the overall success rate after a single session was 78.8% and only 9 patients experienced a median post-operative pain of 4. There was no statistically significant difference between II- and III-degree HD in terms of success rate and complications.…”
supporting
confidence: 92%
“…Regarding the former, there is a huge difference based on the approach. For the endoscopic approach, a 23G needle [ 4 ] is often used while for the transanal approach, the ideal is a 20G needle [ 5 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2007, sclerotherapy received a new impetus with the introduction of 3% polidocanol foam as a sclerosing agent by Moser (75). Since then, several studies have shown the superiority of foam in terms of effectiveness and reduced complications compared with oil-based agents, inaugurating a new era for sclerotherapy (76)(77)(78)(79). However, these studies mainly focused on the treatment of 1-degree HD, while further studies are needed on 2-and 3-degree HD (79,80).…”
Section: St Centurymentioning
confidence: 99%
“…In the treatment of GI hemangiomas, esophageal varices sclerotherapy, internal hemorrhoid sclerotherapy, and intestinal hemangioma sclerotherapy have been reported[ 4 - 6 ]. In a case of using sclerotherapy to control bleeding, it was mentioned that sclerotherapy with 3% polidocanol foam induces an inflammatory reaction with sclerosis of the submucosal tissue and consequent suspension of the hemorrhoidal tissue[ 7 ]. Markovic et al [ 8 ] reported that sclerotherapy in the treatment of low flow vascular malformations did not significantly change hemodynamic consequences and reduce complications.…”
Section: Introductionmentioning
confidence: 99%